Analysis of Stenotrophomonas maltophilia infections in lower respiratory tract samples at a university hospital: 5 year data (Bangladesh Journal of Medical Science, 2024)
Objectives Patients with reported Stenotrophomonas maltophilia (S. maltophilia) growth in lower respiratory tract samples were investigated. The results of these patients were assessed by clinicians as either infection or colonization. The data of patients considered to have S. maltophilia infection were compared to those considered to have colonization to explore factors associated with infection. Methods Parameters including as age, length of hospital stay, duration of S. maltophilia growth after hospital admission, sex, unit, department, specimen type, mechanical ventilation treatment status, antimicrobial susceptibility results, comorbidities, survival, and antimicrobials used during the period from hospital admission to S. maltophilia growth were investigated. Additionally, some biochemical parameters that were examined include the day of hospital admission, the day of sample collection when the bacterium was isolated (±1 day), and the day of discharge/died. Results The infection group had a significantly higher rate of admissions to internal medical departments and more cases of discharge/died. The infection group showed a lower amount of aminoglycoside antibiotic usage and significantly higher levels of BUN, creatinine, neutrophils, and neutrophil-to-lymphocyte ratio on their day of discharge/died. Conclusion Being admitted to internal medical departments and receiving aminoglycoside treatment were identified to be factors associated with S. maltophilia infection. These patients should be monitored for infection markers such as CRP and neutrophil count, as well as renal function tests. It should be noted that being infected with S. maltophilia is an independent risk factor for mortality.Bangladesh Journal of Medical Science Vol. 23 No. 04 October’24 Page : 1095-1103